An overview of invasive micropapillary carcinoma of the breast: past, present, and future - Qiu, Pu; Cui, Qiuxia; Huang, Shengchao; Zhang, Yuanqi; Zhang, Haitao; Luo, Hui (Frontiers in Oncology, 2024)
Invasive micropapillary carcinoma of the breast (IMPC) exhibits a unique micropapillary structure and “inside-out” growth pattern. Despite its extremely low incidence, IMPC has attracted considerable attention owing to its poor prognosis. Since Siriaunkgul and Tavassoli first proposed the term IMPC in 1993 to describe its morphological characteristics, with tumor cell clusters arranged in a pseudopapillary structure within the glandular cavity, its diagnostic rate has substantially increased. Based on the in-depth study of IMPC, a more comprehensive understanding of its epidemiology, clinicopathological features, and diagnostic criteria has been achieved in recent years. The pathogenesis and specific therapeutic targets of IMPC remain unclear. However, numerous studies have delved into its high-risk biological behavior. This review discusses the opportunities and challenges associated with IMPC.